PENYULUHAN METODE BIOPORI SEBAGAI UPAYA PENCEGAHAN BANJIR DI KELURAHAN TEGAL RATU KECAMATAN CIWANDAN KOTA CILEGON - Handayani, Riny; Jumiati, Ipah Ema (Universitas Sultan Ageng Tirtayasa, 2018)
Abstract The impact of flooding on the Community of Tegal Ratu Village, Ciwandan District, Cilegon City is not only in the form of property and building losses. Flooding also affects the economy of society and the development of society as a whole, especially health and education, especially for women. From an average of 100 patients per day, more than 50% of patients are children and women, they are affected by itching, diarrhea and Acute Respiratory Infection (ARI) (Cilegon City Health Office, 2012). They have the ability which is minimal to avoid flooding and women are part of the most severely affected socio-economic community due to limited ability to deal with floods (Media Indonesia, February 25, 2008). Community empowerment in Tegal Ratu Village, Ciwandan District, Cilegon City in the face of flood disasters is felt to be very important because they are the first victims of flooding, so they should be prepared and full material and non-material debriefing to deal with floods. The manufacture of infiltration wells (biopori) is an alternative method for flood prevention, especially in urban areas. It is expected that if the community actively participates in the handling of flood disasters with each house having a biopori well, the soul will have a place to live so far as possible to protect the area against the threats and impacts of disasters, especially floods that are almost routine. if there is high intensity of rain in Tegal Ratu Village, Ciwandan District, Cilegon City.